High Temperature Oxidation of Alumina Forming Cast Austenitic Stainless Steels Within an Environment of Pure Steam - (:unkn) unknown (My University, 2016)
Steam cracking of hydrocarbons in the petrochemical industry is a multibillion dollar industry. The processes performed in these plants create byproducts that negatively affect the integrity of stainless steel piping through high temperature corrosion. Alloys used presently in industry rely on the formation of chromium oxide (chromia) as a protective layer between the bulk metal pipe and chemical byproducts. However, chromia can become susceptible to attack from aggressive species such as carbon, water vapor, and sulfur compounds, thus creating a need for a better protection method. A new series of austenitic stainless steels have been developed in recent years that, rather than forming chromia, create a protective layer of aluminum oxide (alumina) under oxidative conditions. These alloys have high nickel content for the stabilization of the austenitic phase, and a more thermodynamically stable oxide layer relative to the traditional chromia formers. Consequently, alumina forming alloys have been proposed as replacements for chromia forming alloys in the petrochemical industry. General oxidation testing has been performed on alumina forming alloys under dry and 10% water vapor conditions. However, oxidation conditions in industry resemble a 100% steam environment. Therefore, test methods to mimic such conditions are needed so that alloys can be tested and developed further for these applications. Four alloys with aluminum contents ranging from 2.6 to 3.9 wt% were cut from centrifugally cast pipes and subjected to oxidation in an environment of pure steam for up to 30 hours, at temperatures of 800 °C and 950 °C. Samples were analyzed using Raman, SEM, and EDS and showed a continuous alumina layer free of cracks. The alumina layer thickness increased with time. Additionally, larger thicknesses were observed in samples oxidized at 950 °C from those of 800 °C. Thickness measurements were used to calculate parabolic and non-parabolic oxidation rate constants. Samples were compared using calculated parabolic and modified parabolic rates of oxidation. Plots for the prediction of oxide layer thickness were generated both for the Wagner model of parabolic oxidation, and an experimentally determined modification to said model. Oxide scale thickness as formed in pure steam was shown to be related to the aluminum content of the alloy and the temperature and time of exposure. Further testing of alumina forming stainless steels in other concentrations of steam would allow for the determination of steam’s effect on alumina formation kinetics. In addition, tests at additional temperatures between 800 and 950 °C would allow for the calculation of activation energies and full understanding of the oxide layer. Finally, the analysis of alumina layer thickness effects on coking performance in a petrochemical application would allow for the potential transition of these alloys into the commercial market.
Keywords: Alumina; Austenitic Alloy; Coking; High Temperature Oxidation; Stainless Steel